(untitled) (Journal of Student Affairs in Africa, 2021)
The highest attrition rates occur among first-year students. Universities have designed different curricular programmes, such as the development of generic skills, to address this challenge. In the medical school at the University of the Free State in South Africa, these skills were incorporated in the MBChB curriculum as an eight credit-bearing module in 2000 and later increased to 12 credits in 2009. To date, the effectiveness of this first-year module in equipping students with generic skills was last determined in 2002. The aim of this research was to determine the perceptions of first-year students regarding the effectiveness of this module in equipping them with generic skills. A questionnaire survey was distributed to 596 first-year medical students each year from 2013 to 2016. A focus group discussion (FGD) was held with 13 students who failed the first year of study in 2016 and had to repeat in 2017. According to the results, most students had a positive perception about the structure and organisation as well as the benefits of the module. However, from the questionnaire results, the overall rating of the effectiveness of the module was not very positive, with 35% of students rating it effective, 45% rating it relatively effective and 20% rating it not effective. However, during the FGD, seven (54%) of the 13 students rated it effective. In the qualitative statements of the questionnaire, a common comment related to the poor rating was about the unnecessary long hours in some sessions. Other comments from the questionnaire were medically related, with some students suggesting more practical and clinical demonstrations. During the FGD, students could not understand why their peers needed practical demonstrations in the first year. The incorporation of generic skills should be contextand discipline-specific and students should be “re-equipped” with certain skills during different stages of the curriculum.